FORMULASI DAN EVALUASI SEDIAAN SAMPO KOMBINASI EKSTRAK BONGGOL PISANG KEPOK (Musa x paradisiaca L.) dan MINYAK KELAPA (Virgin Coconut Oil) - Akbar, Nanda Dwi; Cahyaningrum, Nineeteen Yuliya; Setiyaningsih, Wahyu; Solichah, Ayu Ina; Christina, Odilia Dea (LPPM Sekolah Tinggi Ilmu Farmasi Nusaputera, 2025)
Shampoo is a hair care product that is used to clean the hair and scalp.Shampoo containing natural ingredients can be an alternative for healthy scalp and hair.The saponin content in the kepok banana hump (Musa x paradisiaca L.) can function as a foamer and a combination of coconut oil (Virgin coconut oil) as a moisturizer (emollient).This research aims to formulate and evaluate a shampoo preparation containing banana weevil extract (Musa x paradisiaca L.) and coconut oil (Virgin coconut oil) in the shampoo preparation. This research is an experimental research. In this research, the formulation of kepok banana weevil extract (Musa x paradisiaca L.) 4%, 8% and 12% and coconut oil (Virgin coconut oil) concentrations of 10%, 12% and 15% were carried out. Extract yield was carried out using the maceration method using 96% ethanol solvent with a ratio of 1: 7.5. Evaluation of the physical properties of shampoo includes organoleptic observations, pH determination, specific gravity measurement, foam height measurement, viscosity and homogeneity testing.Data analysis was carried out using SPSS. Based on research on kepok banana weevil extract (Musa x paradisiaca L.)a thick, reddish brown colored extract was obtained, with a distinctive slightly sweet aroma with a yield of 11.4445% from 400 grams of dried banana weevil. The results of the phytochemical screening of the thick extract of banana weevils were positive for containing saponin compounds. The test results for shampoo preparations F1, F2 and F3 have a cream to brownish cream color, a liquid texture and a coconut banana smell, homogeneous preparations, pH range 6.72 – 8.23; has a foam height of 1.8 – 2.3 cm; viscosity 216 – 250 dPas and specific gravity 0.9569 – 1.0272 g/mL. The results of analysis using One Way ANOVA showed a p value <0.05 in foam height, pH value and viscosity for the three formulas, there were significant differences.This research shows that the addition of banana weevil extract (Musa x paradisiaca L.) and coconut oil (Virgin coconut oil) affects the characteristics of the shampoo preparation.